Maternal mortality among women with sickle-cell disease in France, 1996–2009. (November 2015) - Lesage, N.; Deneux Tharaux, C.; Saucedo, M.; Habibi, A.; Galacteros, F.; Girot, R.; Bouvier Colle, M.H.; Kayem, G.
Abstract: Objective: To describe maternal mortality among women with sickle-cell disease in France. Study design: Data from the national confidential enquiry into maternal deaths and from reference centres for sickle-cell disease were examined to identify women with this disease who died in France during 1996–2009. The maternal mortality ratio among women with sickle-cell disease was estimated and compared with the ratio in the general population. Characteristics of these women and their pregnancies and circumstances of their deaths were examined in detail. Results: Fifteen maternal deaths occurred among an estimated 3300 live births to women with sickle-cell disease, for a maternal mortality ratio of 454 per 100 000 live births (95% CI [254; 750]), versus 9.4/100 000 in the general population. Ten women were homozygous (SS) for sickle-cell disease, and five were composite heterozygotes. The episode leading to death appeared in the antepartum period for seven women (47%). Two women died of septic shock during pregnancy, one at 6 weeks, the other at 24 weeks. The other 13 women (87%) died postpartum. Thirteen deaths were directly attributable to sickle-cell disease. The other two maternal deaths, both considered direct obstetric causes, were due to amniotic fluid embolism and septic shock after post-amniocentesis chorioamnionitis. The expert committee on maternal mortality judged seven of these 15 deaths (47%) to be avoidable. Conclusion: Sickle-cell disease is responsible for a major excess risk of maternal death in France, due mainly to direct complications of the disease.